WOMEN IN THE EYES OF FOOTBALL FANS: WARM, COMPETENT, ADMIRABLE - Javakhishvili, Nino; Butsashvili, Nino; Vardanashvili, Irina; Tordua, Khatia (Georgian Psychological Journal, 2022)
The study investigated attitudes of Georgian football fans towards women using the stereotype content model/SCM on a single sample/single group design. It was conducted with three aims in mind: ﬁ rst was to compare individual and group perspective stereotypes and emotions, the second aim was to look at the attitudes of traditional patriarchal sub-group of football fans and the third was to ﬁ nd how emotions to a group are elicited. The data was collected from 145 participants using the modiﬁ ed version of the SCM questionnaire. The ﬁrst ﬁnding of the study is that women assessed from an individual perspective are considered warmer and more competent than women assessed from the cultural perspective. At the same time, in both cases women were assigned to the HC-HW cluster and the same three positive emotions of admiration, sympathy and pride were elicited, meaning that even patriarchal group of football fans hold very positive attitudes to women. This ﬁ nding is supported by the third one that not only competence and warmth but their interaction predicts pride towards women. It also enriches our understanding of how emotions are linked to the stereotypes: warmth elicits pride depending on competence and vice versa. Certain levels of both competence and warmth are needed to elicit pride, while if one of the stereotypes is high enough, the help of the other is not needed.